Fünf Schritte vorwärts - Spann, Meno, 1903-; Leopold, Werner F., 1896- (Boston, Heath, 1956)
book 1. Der Gorilla Goliath.--book 2. Am Radio.--book 3. Die Nibelungen.--book 4. Doktor Faust.--book 5. Wallenstein.
"Third series of Hagbolts Graded German readers."
Each book, previously published separately, has special tip.
Keywords: German language -- Readers